Kronecker sum of binary orthogonal arrays - Sinha K.; Vellaisamy P.; Sinha N. (Utilitas Mathematica, 2008)
Kronecker sum of binary orthogonal arrays have been introduced. It is well known that for any t ≥ 2, O A(2t,t + 1,2, t) exists. We give conditions under which OA(2t, t+1,2, t) is self-conjugate, and show the existence of mixed OA(2t,n x 2t+1,2). Also, we prove that the existence of O A(N, k, 2, t′), t′ ≥ 2, implies the existence of OA(N2t k(t+l), 2, p), which is a-resolvable, and obtain mixed OA(N2t,n × 24k(t+1), p) therefrom, where p = 2 if max(t, t′) = 2, and p = 3 if max(t, t ′) > 3, where t corresponds to the trivial OA(2t, t + 1,2, t).